Prevalencia de sarcosporidiosis sarcocystis spp por inspección en bovinos sacrificados en el camal municipal de Pasaje - Velepucha Caiminagua, Henry J. (2005)
The present investigation was carried out it in the Municipal Camal of the Canton Pasaje between the months of August and September of the 2005 being inspected a bovine total of 970 of which 287 were positive and 683 negatives giving a prevalencia of 29,59%. The biggest prevalencia for age registers in the animals understood among the 2 to 5 years (14,95%), continued by the adults to 5 years (14,12%) and finally the smallest animals to 2 years of age (0,52%). The seemingly more susceptible race to the illness is the mestizo (17,73%), followed by the Holstein (4,95%), Criolla (3,20%), Brown Swiss (2,27%), Brahman (1,34%) and finally the Jersey (0,10%). 53,4% of the sacrificed animals was female (518), and 46,6% males (452), with a prevalencia of 14,95% (145) and 14,64% (142) respectively. The countries of El Oro and Azuay are those that present bigger prevalencia: 21,65% and 7,63% respectively. As for the cantons that of more prevalencia is Zaruma (7,53%), followed by Chilla (7,11%), Pucará (6,81%), Pasaje (4,64%) and Atahualpa (1,44%).